Mathematical model of induction motor containing slot harmonics effect in magnetic field and various types defects presence - V. V. Kharlamov; A. V. Sklyar; D. I. Popov; A. V. Eroshenko (Омский научный вестник)
The article presents mathematical model of induction motor taking into account the appearance of the slot harmonics in the air gap magnetic field induction. This model can be used in the development of stator current spectrum analysis methods. There are presented the results of low power induction motor mathematical modeling with various types faults. The conclusion is made about spectrum-current analysis possibility to determine the induction motor rotor speed in the presence of defects.